A picture book of Thomas Jefferson - Adler, David A.; Wallner, John C.; Wallner, Alexandra (New York : Holiday House, 1990)
Traces the life and achievements of the architect, bibliophile, president, and author of the Declaration of Independence
AD 700
Keywords: Jefferson, Thomas, -- 1743-1826 -- Juvenile literature; Jefferson, Thomas, -- 1743-1826.; Presidents -- United States -- Biography -- Juvenile literature; Presidents